2021
DOI: 10.1111/jcmm.16661
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 deficiency aggravates angiotensin II‐induced hypertensive cardiac injury by the impairment of lymphangiogenesis

Abstract: Lymphangiogenesis is possibly capable of attenuating hypertension‐induced cardiac injury. Sirtuin 3 (SIRT3) is an effective mitochondrial deacetylase that has the potential to modulate this process; however, its role in hypertension‐induced cardiac lymphangiogenesis to date has not been investigated. Our experiments were performed on 8‐week‐old wild‐type (WT), SIRT3 knockout (SIRT3‐KO) and SIRT3 overexpression (SIRT3‐LV) mice infused with angiotensin II (Ang II) (1000 ng/kg per minute) or saline for 28 days. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Sirtuin-3 overexpression or cotreatment with a VEGF-C variant, engineered for VEGFR-3 specificity, enhanced lymphangiogenesis, and decreased cardiac injury and fibrosis in Ang II-infused animals compared with controls. 98,99 VEGF-C also improved fluid clearance in the heart, reduced inflammation after 1 week, and decreased inflammation and BP, as confirmed by telemetry, after 4 weeks of treatment. 99 Salt-based models revealed similar findings.…”
Section: Lymphatics Of the Heart In Hypertensionmentioning
confidence: 59%
“…Sirtuin-3 overexpression or cotreatment with a VEGF-C variant, engineered for VEGFR-3 specificity, enhanced lymphangiogenesis, and decreased cardiac injury and fibrosis in Ang II-infused animals compared with controls. 98,99 VEGF-C also improved fluid clearance in the heart, reduced inflammation after 1 week, and decreased inflammation and BP, as confirmed by telemetry, after 4 weeks of treatment. 99 Salt-based models revealed similar findings.…”
Section: Lymphatics Of the Heart In Hypertensionmentioning
confidence: 59%
“…Interestingly, the overexpression of Sirtuin 3 stimulates the expression of Ang-1/Tie-2 while reducing the expression of ang2 [38,39]. Additionally, Sirtuin 3 overexpression induces the expression of HIF2α and Notch3 [38,39]. Based on the above experimental evidence, it suggests that the induction of HIF2α may limit inflammation and promote endothelial cell survival by preserving the barrier integrity (Figure 2).…”
Section: Hif2a Expression and Inflammationmentioning
confidence: 93%
“…Mechanistically, LPS stimulation suppresses the expression of Sirtuin-3, HIF2α, and Notch3 while promoting the expression of PHD2 and ang2 (Figure 2). Interestingly, the overexpression of Sirtuin 3 stimulates the expression of Ang-1/Tie-2 while reducing the expression of ang2 [38,39]. Additionally, Sirtuin 3 overexpression induces the expression of HIF2α and Notch3 [38,39].…”
Section: Hif2a Expression and Inflammationmentioning
confidence: 98%
“…SIRT3 is a major mitochondrial deacetylase closely associated with angiogenesis. A recent study indicated that SIRT3 activation upregulates the VEGF-C-VEGFR3 signaling axis protein expression, thereby promoting migration and proliferation of lymphatic endothelial cells (LECs), and lymphangiogenesis in AngⅡ-induced hypertensive heart models ( 73 , 74 ). Details are provided in Table IV and Fig.…”
Section: Lymphangiogenesis and Cardiovascular Diseasementioning
confidence: 99%